Phenomenon-Based Learning Improves Self-Discipline and Work Team Competence in Social Sciences Learning - Anak Agung Istri Dewi Adhi Utami; I Nyoman Tri Esaputra; I Gusti Ayu Agung Manik Wulandari (Universitas Pendidikan Ganesha, 2024)
Social studies learning activities for elementary school students currently need more self-discipline and competence in teamwork. Even though this ability is required for the 21st century, based on these problems, this research aims to test the influence of the phenomenon-based learning model on self-discipline and teamwork competencies in social studies learning. The type of research used is Quasi-Experimental Design (quasi-experiment) with a posttest-only control group design. The population in this study was all elementary school students, totalling 192 students. The sample for this research was taken randomly (random sampling) with a total sample of 58 students. The method used to collect data is a questionnaire. The instrument used to collect research data was a questionnaire sheet. The analysis used to test the hypothesis is two-way ANOVA. The research results show a significant effect simultaneously and partially with a sig value. < 0.05, there is an influence of Phenomenon Based Learning on self-discipline and teamwork competency in Social Sciences Learning. This research implies that the application of Phenomenon Learning can make it easier for students to learn social studies, which impacts increasing student competence.